2019
DOI: 10.1038/s41598-019-46114-x
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Renin-Angiotensin-System Dysregulation after Kidney Transplantation

Abstract: Angiotensin-converting enzyme inhibitors (ACEis) are beneficial in patients with chronic kidney disease (CKD). Yet, their clinical effects after kidney transplantation (KTx) remain ambiguous and local renin-angiotensin system (RAS) regulation including the ‘classical’ and ‘alternative’ RAS has not been studied so far. Here, we investigated both systemic and kidney allograft-specific intrarenal RAS using tandem mass-spectrometry in KTx recipients with or without established ACEi therapy (n = 48). Transplant pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, earlier studies on the distribution of NEP using whole organs and northern blot analyses showed that NEP mRNA expression levels were abundant in the kidney and lung, which were both much higher than heart. 27 However, histochemical examination revealed that NEP was mainly expressed in tubular epithelial cells in kidney 28,29 and in bronchial epithelial cells in lung, 17,30 which suggests that NEP expressed in these cells in kidney or lung could not be in direct contact with circulating natriuretic peptides. In contrast, NEP expressed in cardiomyocytes, fibroblasts, and capillary endothelial cells in heart would be in direct contact with ANP and BNP just after secretion from cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…However, earlier studies on the distribution of NEP using whole organs and northern blot analyses showed that NEP mRNA expression levels were abundant in the kidney and lung, which were both much higher than heart. 27 However, histochemical examination revealed that NEP was mainly expressed in tubular epithelial cells in kidney 28,29 and in bronchial epithelial cells in lung, 17,30 which suggests that NEP expressed in these cells in kidney or lung could not be in direct contact with circulating natriuretic peptides. In contrast, NEP expressed in cardiomyocytes, fibroblasts, and capillary endothelial cells in heart would be in direct contact with ANP and BNP just after secretion from cardiomyocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Renal sodium retention may be worsened by the use of immunosuppressive regimens, mainly corticosteroids[ 48 ] and calcineurin inhibitors (CNIs)[ 49 ] as well as during episodes of acute rejection, probably indicating ischemic allograft damage[ 50 ]. Dysregulation of the renin-angiotensin-aldosterone system[ 51 ] and sympathetic nerve overactivity, driven in the early post transplantation period by the native kidneys (since the graft is initially denervated before becoming later re-innervated[ 52 ]), also lead to increased peripheral vascular resistance and development of hypertension[ 5 , 53 , 54 ]. Increased arterial stiffness, endothelial dysfunction and imbalance between vasoconstrictive and vasodilating agents are also pertinent to CKD and further contribute to increased BP[ 55 , 56 ].…”
Section: Pathophysiology Of Hypertension In Ktrsmentioning
confidence: 99%
“…In their study, Kovaric et al hypothesized that, in the first months, AngII occurs in the graft through moderate ACE activity, while Ang 1–7 formation occurs through NEP and ACE-mediated AngII (from AngI). Several years later, chymase activity becomes prominent and takes over the previously ACE-mediated AngII formation, alongside the persisting NEP-mediated Ang 1–7 formation [ 188 ].…”
Section: Part 3: Ras and Transplantationmentioning
confidence: 99%